Water circulation and impact on water quality in the southwest of Efate Island, Vanuatu. (December 2021) - Faivre, Gaelle; Sami, Erie; Mackey, Brendan; Tomlinson, Rodger; Zhang, Hong; Kotra, Krishna Kumar; Aimbie, Jim; Maniel, Michael; da Silva, Guilherme Vieira; Rand, Emily
Abstract: In Small Island Developing States (SIDS), water pollution is not monitored or assessed frequently enough to fully understand the processes, impacts of water quality issues and what solutions are available This study investigated flushing time in Erakor lagoon and Port Vila Bay, Vanuatu using a numerical model developed in Delft3D. Microbial contamination by Escherichia coli was detected in multiple locations in the lagoon system with counts exceeding thresholds related to human health concerns. Modelling demonstrated a poor flushing time overall with a further decrease as the influence of waves and wind increased, especially in Vila Bay. Sea level rise resulted in an increase in flushing time downstream of the lagoon near the open sea, while with a decrease upstream and in Vila Bay. Based on these results, we recommend long-term continuous monitoring and identification of higher risks areas to prioritise decisions around wastewater management. Highlights: Erakor Lagoon and Vila Bay have both high residence times. Erakor lagoon is highly influenced by the waves, sea levels and the tidal flow. Sampling revealed E. coli exceeding human health thresholds in Erakor lagoon. Monitoring on a real-time would increase the capacity building. The flushing time in Vila Bay is influenced by the wind but not by the dredging.